2017
DOI: 10.1007/s12613-017-1381-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cu–Ti powder metallurgical materials

Abstract: Powder metallurgical Cu-Ti alloys with different titanium additions produced by hot pressing were characterizied by optical microscopy, scanning electron microscopy, X-ray diffraction analysis, and hardness, wear and bending tests. The addition of titanium to copper caused the formation of different intermetallic layers around the titanium particles. The titanium content of the intermetallics decreased from the center of the particle to the copper matrix. The hardness, wear resistance and bending strength of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 40 publications
4
5
0
Order By: Relevance
“…The hardness results are in accordance with the behavior observed by previous investigations where the titanium increase had a positive effect on the hardness value, especially in values higher than 5% [8,42,48]. The studies carried out by Akbarpour et al [20] present a close reference to the hardness values found in the composites, despite the need for an aging process in order to promote intermetallic growth and the elimination of the thermal stress of the sintering to the extent that ideal values proposed by Shon et al [49].…”
Section: Microhardness Of the Materialsupporting
confidence: 92%
See 2 more Smart Citations
“…The hardness results are in accordance with the behavior observed by previous investigations where the titanium increase had a positive effect on the hardness value, especially in values higher than 5% [8,42,48]. The studies carried out by Akbarpour et al [20] present a close reference to the hardness values found in the composites, despite the need for an aging process in order to promote intermetallic growth and the elimination of the thermal stress of the sintering to the extent that ideal values proposed by Shon et al [49].…”
Section: Microhardness Of the Materialsupporting
confidence: 92%
“…Similar tribological systems of interaction between parts with intermetallics of the laminar type in the titanium particles and the friction generated by a steel pin had been observed in previous studies [42], evidencing that the increase of titanium has a positive effect on the decrease of wear rates and wear coefficient. In addition, the increase of intermetallic layers as described by Yan et al [33] has a positive effect under wear conditions in cause of the compacted oxide films formation by the wear processes on the surface and greatly reduce the wear rate between the friction counterparts.…”
Section: Tribological Behaviorsupporting
confidence: 84%
See 1 more Smart Citation
“…Although copper possesses good properties because of its ductile nature, it has poor mechanical properties and this restricts structural applications [5][6][7]. To overcome the aforementioned disadvantage, copper is reinforced with Al 2 O 3 , SiC, TiO 2 , Gr, ZrO 2 , Ti, TiB, TiB 2 , TiC, and fly ash particles to form copper matrix composites which improved the mechanical properties [2,[8][9][10][11][12][13]. Most manufacturing companies focus on copper matrix composites to produce several components due to the supreme properties over other matrix composites [14].…”
Section: Introductionmentioning
confidence: 99%
“…But the main drawback of this alloy, which has limited its industrial use, is the high cost and toxicity of beryllium [7]. Cu-Ti alloys are the best alternative to Cu-Be and some similar alloys, because of the high strength, corrosion resistance, antibacterial property, high electrical conductivities and thermal stability [2,[8][9][10][11]. Some applications of Cu-Ti nanocomposite include relay controls [12], prosthetic dental applications [13], solar cells [14], anticorrosive applications [15], electrochemical denitrification [16], and, etc .…”
Section: Introductionmentioning
confidence: 99%